Inferring market power from retail deposit interest rates in the euro area - Laura Vajanne (Bank of Finland, 2009)
This paper tests for the existence of market power in banking, using data on demand deposit rates of households and corresponding market rates in five euro area countries. An implicit measure for market power is based on a partial adjustment model that also allows for an asymmetric response of deposit rates to changes in market rates. The period covers the ten years since introduction of the euro. The analysis indicates that banks are exercising major market power within the euro area. In addition to general sluggishness, bank deposit rates reactions are clearly asymmetric: flexible when market rates are decreasing and rigid when rates are increasing. The degree of asymmetric behaviour can be interpreted as a further indication of the market power banks exercise. Despite country differences, a general pattern of interest rate adjustment in demand deposit pricing is observable.
URN:NBN:fi:bof-20140807371
Keywords: 330